2020
DOI: 10.1002/cbic.202000319
|View full text |Cite
|
Sign up to set email alerts
|

Nonhydrolyzable Heptose Bis‐ and Monophosphate Analogues Modulate Pro‐inflammatory TIFA‐NF‐κB Signaling

Abstract: d-Glycero-d-manno-heptose-1β,7-bisphosphate (HBP) and dglycero-d-manno-heptose-1β-phosphate (H1P) are bacterial metabolites that were recently shown to stimulate inflammatory responses in host cells through the activation of the TIFAdependent NF-kB pathway. To better understand structurebased activity in relation to this process, a family of nonhydrolyzable phosphonate analogues of HBP and H1P was synthesized. The inflammation modulation by which these molecules induce the TIFA-NF-kB signal axis was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Acting as an inflammation‐related adaptor protein, TIFA plays a vital role in various biological processes that include signal transduction in innate immunity, 9 , 38 , 39 , 40 , 41 inflammation, 42 , 43 hypoxia reoxygenation, 44 and cancer. Previous studies proved that TIFA plays different roles in various cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acting as an inflammation‐related adaptor protein, TIFA plays a vital role in various biological processes that include signal transduction in innate immunity, 9 , 38 , 39 , 40 , 41 inflammation, 42 , 43 hypoxia reoxygenation, 44 and cancer. Previous studies proved that TIFA plays different roles in various cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the above results indicated that TIFA-mediated RSK signaling and PRAS40/mTOR signaling were mutually independent in an AKT/IKK-independent manner. Based on our findings, we propose the following model (Figure 7I Acting as an inflammation-related adaptor protein, TIFA plays a vital role in various biological processes that include signal transduction in innate immunity, 9,[38][39][40][41] inflammation, 42,43 hypoxia reoxygenation, 44 and cancer. Previous studies proved that TIFA plays different roles in various cancer types.…”
Section: Proposed Mechanism and Model Of Tifa Promotes Crc Cell Proli...mentioning
confidence: 95%
“…Noteworthy contributions include Sauvageau et al's synthesis of probes and derivatives to elucidate the inflammatory pathway induced by HBP, 6,7 and Vincent et al's synthesis of biotinylated analogs for identifying pathogen recognition receptor (PRRs) of bacterial metabolites, 8 and hydrolysis-resistant HBPs by substituting the anomeric oxygen with fluoromethylene. 9 We were also captivated by its intriguing bioactivity, prompting us to embark on the synthesis of the D-glycero-Dmanno-heptose skeleton and HBP through an innovative strategy.…”
mentioning
confidence: 99%
“…We assumed that, under this condition, the products could be epimerized at the α-positions of C-4-ketone, affording a mixture of diastereomers. As another option, the Mitsunobu phosphorylation of 7 was conducted . Despite several attempts, we were unable to obtain the desired 13 except that multicomponent mixtures were detected.…”
mentioning
confidence: 99%